2007
DOI: 10.2139/ssrn.998324
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment Effectiveness and Side-Effects on Prescription Decisions: The Role of Patient Heterogeneity and Learning

Tat Y. Chan,
Chakravarthi Narasimhan,
Ying Xie

Abstract: The goal of a standard clinical study is to assess the mean or median effectiveness and side effects of drugs through randomized clinical trial experiment. In this paper we argue that, it is important to understand how physicians and patients evaluate the effectiveness and side effects. Second, it is also important to understand the extent of heterogeneity in these outcomes across patients, especially when physicians and patients are risk averse in choosing treatments. Finally, using data from a market environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Researchers in marketing and economics have studied the impact of firms’ marketing activities (e.g., detailing) and feedback from patients on the diffusion of new drugs within and across physicians (see Manchanda et al 2005). Given the possibility that physicians might be uncertain about the quality of the new drug, researchers have typically assumed physicians learn about drug quality in a Bayesian way, with detailing and patient feedback providing the information for such learning (e.g., Chan, Narasimhan, and Xie 2007; Currie and Park 2002; Narayanan and Manchanda 2009). Various researchers have demonstrated that physicians learn from multiple sources of information (e.g., Ching 2010a, b; Ching and Ishihara 2010, 2012; Coscelli and Shum 2004; Narayanan and Manchanda 2009; Narayanan, Manchanda, and Chintagunta 2005) and that physicians are willing to sacrifice current utility by experimenting with a new drug to obtain information that enables them to make better future decisions (e.g., Crawford and Shum 2005; Ferreyra and Kosenok 2011).…”
mentioning
confidence: 99%
“…Researchers in marketing and economics have studied the impact of firms’ marketing activities (e.g., detailing) and feedback from patients on the diffusion of new drugs within and across physicians (see Manchanda et al 2005). Given the possibility that physicians might be uncertain about the quality of the new drug, researchers have typically assumed physicians learn about drug quality in a Bayesian way, with detailing and patient feedback providing the information for such learning (e.g., Chan, Narasimhan, and Xie 2007; Currie and Park 2002; Narayanan and Manchanda 2009). Various researchers have demonstrated that physicians learn from multiple sources of information (e.g., Ching 2010a, b; Ching and Ishihara 2010, 2012; Coscelli and Shum 2004; Narayanan and Manchanda 2009; Narayanan, Manchanda, and Chintagunta 2005) and that physicians are willing to sacrifice current utility by experimenting with a new drug to obtain information that enables them to make better future decisions (e.g., Crawford and Shum 2005; Ferreyra and Kosenok 2011).…”
mentioning
confidence: 99%
“…In the pharmaceutical market, increased demand for a product may also increase the risk of gaining patients who experience adverse drug reactions, leading to an increased risk of regulatory intervention by the FDA or litigation, leading pharmaceutical companies to internalize the full costs of their actions (Chan et al, 2007;Narayanan and Manchanda, 2009;Ching and Ishihara, 2010).…”
Section: Introductionmentioning
confidence: 99%